Biological Control of Wheat Root Rot Caused by Fusarium SPP Using Microbial Biocontrol Agents - Hamzah A. Yasir (Universitas Negeri Malang, 2026)
This study aimed to evaluate the ability of the fungus Trichoderma harzianum and the bacteria Bacillus subtilis to resistant disease Wheat root rot caused by the fungus Fusarium culmorum. The pathogenic fungus was isolated from the roots of diseased wheat plants, and the effect of two biological agents on it was tested in vitro and under greenhouse conditions. The laboratory results showed that Trichoderma was superior in inhibiting the growth of the pathogenic fungus 77.29% followed by Bacillus with a rate of 69.64%, while the use of both biocontrol agents showed 82.94% and the average diameter of F.culmorum was 19.3 with T.harzianum, followed by B. subtilis, it was 25.8, while in treatment of both biocontrol agents was 14.5 compared to control treatment which was 85. In greenhouse experiments, the disease severity was 21.4% in plants treated with T.harzianum and the reduction percentage damage was 74.2%, while it was 28.6% in the treatment with Bacillus, and the reduction percentage damage was 65.6%. The treatment with both biocontrol agents was 17.6% and the reduction percentage of damage was 78.8% compared to control (C2) the disease severity was 83.2%. These results suggest that Trichoderma and Bacillus can be used to control wheat root rot instead of chemical pesticides. Field trials are recommended to confirm these findings and to develop biocontrol agents.